2019
DOI: 10.32807/jkt.v1i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Life Review Therapy Terhadap Kemampuan Kognitif Lansia Demensia Di PSTW Puspakarma Mataram

Abstract: Melihat kembali kehidupan sebelumnya (Life Review Therapy) merupakan proses yang normal berkaitan dengan pendekatan terhadap proses kematian. Reintegrasi yang sukses dapat memberikan arti dalam kehidupan dan mempersiapkan seseorang untuk mati, tanpa disertai rasa cemas dan rasa takut. Hasil diskusi terahir tentang proses ini, menemukan melihat kembali kehidupan sebelumnya merupakan salah satu strategi untuk merawat masalah jiwa lansia. Desain penelitian ini, adalah Quasi Eksperiment dengan pendekatan One Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…By evaluating life accomplishments, individuals can perceive them as sources of wisdom or confront the end of life with regrets and other negative emotions. Life Review plays a crucial role in facilitating positive growth and adjustment in old age, aiding individuals in finding purpose in their life journey and attaining peace in facing the future (Emilyani & Dramawan, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By evaluating life accomplishments, individuals can perceive them as sources of wisdom or confront the end of life with regrets and other negative emotions. Life Review plays a crucial role in facilitating positive growth and adjustment in old age, aiding individuals in finding purpose in their life journey and attaining peace in facing the future (Emilyani & Dramawan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Research by Emilyani and Dramawan, which assessed the effectiveness of LRT on elderly cognitive changes, involved participants receiving treatment in four sessions: 1) discussing childhood experiences, 2) discussing teenage experiences, 3) discussing adult experiences, and 4) discussing experiences from advanced age. They concluded that after undergoing LRT, there was an improvement in cognitive ability levels (Emilyani & Dramawan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sedangkan puzzle yang akan peneliti gunakan dalam penelitian ini adalah modifikasi puzzle yang dibuat dan didesain khusus dengan mengacu pada metode life review therapy. Mengingat pada masa lansia adalah fase akhir kehidupan, dimana mereka harus mempersiapkan diri menghadapi masa tua tanpa disertai rasa cemas dan rasa takut (Emilyani & Dramawan, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Elderly is someone who has reached the age of 60 and over and is part of the community who is at risk of experiencing a decline in health. Health changes that occur in the elderly include: physiological changes, decreased function, affective disorders, cognitive disorders, and psychosocial disorders (Emilyani and Dramawan, 2019).…”
Section: Introductionmentioning
confidence: 99%